Molecular identification of cryptic diversity in species of cis-Andean Mylossoma (Characiformes: Serrasalmidae) - Mateussi, Nadayca T. B. [UNESP]; Pavanelli, Carla Simone; Oliveira, Claudio [UNESP] (Taylor & Francis Ltd, 2017)
Mylossoma is a Serrasalmidae genus with only two current valid species in the cis-Andean region but with several available names, today considered as junior synonymous. Morphological information combined with single-locus DNA sequences of cytochrome c oxidase I gene analysed by Barcode Index Number and General Mixed Yule Coalescent model were used in the present study to help the recognition of Operational Taxonomic Units (OTUs) in cis-Andean Mylossoma and discuss species boundaries within the genus. Five OTUs were recognized based on both morphological and molecular approaches. The analysis using the Barcode Index Number resulted in five OTUs, with M. duriventre being split in one unity in the Amazon, one in the Orinoco, one in Parana-Paraguay and one in Tocantins-Araguaia which is coherent with our morphological results.
Keywords: DNA barcoding; GMYC; neotropical; species complex